IMPLEMENTASI MEDIA BERBASIS TEKNOLOGI INFORMASI SEBAGAI MEDIA PEMBELAJARAN OLEH GURU BIOLOGI DI SMA NEGERI SE-KABUPATEN DELI SERDANG - Jhonas Dongoran; Dian Arisetya (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2018)
This study aims to describe the availability of IT-based learning media in Deli Serdang District High School. This study uses a type of quantitative research with descriptive methods. the population is all Se-regency district biology teachers. The subjects in this study were biology teachers in class XI. From the results of the questionnaire regarding the completeness of IT-based learning media for Tanjung Morawa 1 Public High School, Percut Seituan 1 Public High School, and 1 Pancur Batu Public High School obtained a percentage of 55.56% and for Namorambe 1 Public High School, Bangun Purba 1 Public High School and Public High School 1 Galagng obtained a percentage of 44.44%. From the results of the questionnaire regarding the condition of IT-based learning media for Namorambe 1 Public High School amounting to 11.11%, for State High School 1 Percut Sei Tuan, Galan 1 High School and Panacur Batu 1 High School at 55.56%, for Tanjung Morawa 1 Public High School and Bangun Purba 1 Public High School at 33.33%.Keywords: Media, Information Technology, Implementation